Plasma neurofilament light chain protein is not increased in forensic psychiatric populations: a pilot study - Fernqvist, Anja; Alexiou, Eirini; Zetterberg, Henrik; Howner, Katarina; Nilsson, Thomas; Andiné, Peter (Frontiers in Psychiatry, 2023)
Neurofilament light chain protein (NfL) is a fluid biomarker of neural injury measurable in cerebrospinal fluid and blood. Patients with different neurodegenerative disorders and mild traumatic brain injury display elevated levels of NfL. However, so far, elevated levels of NfL have not been demonstrated in persons with psychiatric disorders. To our knowledge, the occurrence of NfL in the blood has not previously been studied in persons undergoing forensic psychiatric assessment or persons treated in forensic mental health services. Supposedly, these persons suffer from experiences and conditions with a higher risk of neural injury than other psychiatric patients. In this pilot study, we investigated plasma levels of NfL in 20 persons undergoing forensic psychiatric assessment and 20 patients at a forensic psychiatric hospital. NfL values were compared with control groups of healthy individuals matched for age and sex. The prevalence of increased NfL in both forensic populations was low and did not differ compared with the controls. However, some persons undergoing forensic psychiatric assessment showed slightly elevated values, which gives reason to look further into this group.